Neuromarketing en la Empresa Angelostore del periodo 2022. - Zúñiga Gavilanes, Angelo Jeampaul (2023)
This case study is about the influence of digital neuromarketing of the company Angelostore, which aims to analyze the process of consumer purchase decision to increase sales in the city of Babahoyo during 2022, for which the importance of knowing some situations that limit the work and in turn alternatives that could make efficient and effective the process of those who are responsible for serving the public with sufficient capacity and knowledge of fact, to thus contribute to the development of the microenterprise. In its methodology, a qualitative approach is proposed, using the analytical-synthetic method, which first analyzes the specific data collected through the collection techniques applied during the survey, with the aim of collecting relevant and concise information, applying data collection techniques such as interviews and surveys through questionnaires in which the difficulties that exist in the company Angelostore, the factors that influence within the company's consumers when buying any product through digital media were evidenced. For which it was suggested that workers should be trained to improve the treatment of customers and implement neuromarketing strategies to increase sales and attract potential customers through the use of digital media.